Consumer behaviour and environmental sustainability. Issue 6 (27th October 2020) - Nguyen, Ninh; Johnson, Lester W.
Abstract: This special issue of the Journal of Consumer Behaviour aims to contribute to the knowledge of the drivers of environmentally sustainable behaviour and the characteristics of green consumers. It consists of eight papers that represent a range of topics related to consumer behaviour and environmental sustainability. The special issue has several implications. First, environmentally sustainable behaviour is influenced by multiple motives and determinants, which include internal, social, situational and demographic factors. Second, the impact of such factors tends to vary across national and consumer context. Third, integrative and comprehensive models including mediators and/or moderators could be used to better understand the mechanism through which the various factors affect pro‐environmental behaviour. Fourth, green marketing initiatives (e.g., sustainable products, green advertising) could be used to promote consumer's pro‐environmental beliefs and behaviours. Finally, interventions aimed at influencing habit and promoting environmentally sustainable behaviour should be tailored to different target groups such as those with different personality dispositions, environmental concerns and levels of engagement in environmental practices at home.